Does Gabapentin Relieve Acute Preoperative Anxiety? - Pathak, L (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: The role of Gabapentin in relieving chronic pain, chronic anxiety disorders and acute postoperative pain is well known by now. Trials done with the administration of Gabapentin to treat preoperative anxiety showed mixed results. So, this study was conducted to test the hypothesis that premedication with Gabapentin 1200 mg versus placebo would reduce preoperative anxiety in patients undergoing open cholecystectomy under general anesthesia. MATERIAL AND METHODS: A prospective, randomized, double blind and placebo controlled study was carried out at Universal College of Medical Sciences & Teaching Hospital (UCMSTH) from August 2012 to Januray 2014. Total 160 adult patients of American Society of Anaesthesiologist (ASA) I and II were divided into 2 groups of 80 each. Patients in group 1 and group 2 received capsules Gabapentin (1200mg) or identical placebo capsules 2 hours prior to surgery respectively. Preoperative anxiety was assessed for three times using Anxiety Visual Analogue Scale (VAS) score. A uniform anesthetic technique was used in both groups. Parameters including preoperative and postoperative sedation scores and various side effects were also observed. RESULTS: VAS anxiety scores after one hour of drug intake (47.19±17.37 versus 63.13±17.77) and just before induction of anaesthesia (43.81±17.72 versus 81.81±21.57) were significantly lower in Gabapentin group as compared to placebo group. No patient experienced any significant side effects or sedation in either group throughout the study period. CONCLUSIONS: Premedication with 1200 mg Gabapentin in open cholecystectomy patients significantly reduced preoperative anxiety as evident by decrease in anxiety VAS scores without any significant side effects. DOI: http://dx.doi.org/10.3126/jucms.v2i3.11821 Journal of Universal College of Medical Sciences Vol.2(3) 2014: 9-14